(untitled) (World Bulletin of Public Health, 2022)
Coronavirus disease 2019, also known as COVID-19, is a new public health emergency that poses a threat to humanity .A strong immune response during viral infections, as well as a SARS-CoV-2, may be required for COVID-19 to be resolved. In severe individuals, however, chronic immune activation can develop to a hemophagocytosis-like condition, with uncontrollable cytokine production. IL-18 is produced by macrophages in the early stages of viral infections .In this study carried out on 100 samples of blood from COVID-19 patients and 20 control both sex (male &female) to determine IL- 18 . In general, the Serum IL-18 levels were remarkably higher in COVID-19 patients compared to healthy individuals (control). Furthermore, the infections were significantly higher in age group ( 70 >80 18 were -IL 18 levels according to their gender-IL while years years old) found to be higher in men than women